Vliyanie intenivnykh fizicheskikh nagruzok na razvitie allergicheskikh zabolevanii - Galiev, R. S. (Teorija i Praktika fiziceskoj Kul'tury, 1999)
Aim of the study eas to investigate the influence of intensive physical loads on the development of allergic diseases of the immediate type. The results show: 1. Daily intensive sports training decreases the possibility of the development of allergies of the immediate type. This can be explained by the decrease of the intensity of the arising of immunologic stage. 2. The phases of restoration after intensive loads over no less than the period of sensibilization are critical for those who have a predisposition for allergic diseases , because in these phases the danger of such diseases is higher.